Mechanical deformation distinguishes tunneling pathways in molecular junctions - Xie, Zuoti; Bâldea, Ioan (Journal of the American Chemical Society, 2019)
Developing a clearer understanding of electron tunneling through molecules is a central challenge in molecular electronics. Here we demonstrate the use of mechanical stretching to distinguish orbital pathways that facilitate tunneling in molecular junctions. Our experiments employ junctions based on self-assembled monolayers (SAMs) of homologous alkanethiols (CnT) and oligophenylene thiols (OPTn), which serve as prototypical examples of σ-bonded and π-bonded backbones, respectively. Surprisingly, molecular conductances (Gmolecule) for stretched CnT SAMs have exactly the same length dependence as unstretched CnT SAMs in which molecular length is tuned by the number of CH2 repeat units, n. In contrast, OPTn SAMs exhibit a 10-fold-greater decrease in Gmolecule with molecular length for stretched versus unstretched cases. Experiment and theory show that these divergent results are explained by the dependence of the molecule-electrode electronic coupling Γ on strain and the spatial extent of the principal orbital facilitating tunneling. In particular, differences in the strain sensitivity of Γ versus the repeat-length (n) sensitivity can be used to distinguish tunneling via delocalized orbitals versus localized orbitals. Angstrom-level tuning of interelectrode separation thus provides a strategy for examining the relationship between orbital localization or delocalization and electronic coupling in molecular junctions and therefore for distinguishing tunneling pathways.
Published: December 8, 2018
Gesehen am 15.05.2019